Developing a New Teaching Model to Promote the Development of Second Graders’ Metacognitive Monitoring - Ma, Yuehuan; Zhou, Ying (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2022)
This paper is an empirical one."Learning to think" is the motivation system for students to "learn mathematics well", is a kind of inner stable cognitive psychological quality, and is the "engine" for the cultivation of innovative consciousness. Guiding students to learn to think plays an important role in mathematics teaching. However, students often do not understand the connection between mathematical knowledge and real life, and do not understand how to use mathematical knowledge to solve problems. In order to let students learn to think, the researchers designed a teaching model composed of "FROM- WHAT-WITH-HOW-CHANGE-HAVE" based on the concept of metacognitive monitoring. This is a new teaching method that uses a set of closely connected problems chains to guide students in solving problems and feel the charm of mathematical knowledge. At the same time, Thirty second grade students from a primary school in Yulin, Guangxi, were selected as the research object. The lesson "designing the best route to visit the zoo" was taken as an example to inspire second grade students to think and answer through the teaching experiment. Through experiments, students’ problem-solving and reflective abilities have been greatly improved. It shows that guiding students to think through real questions can improve students learning ability. In the process of mathematics learning, we must focus on real problems and guide students to think deeply.